Deciphering the Biosynthetic Codes for the Potent Anti‐SARS‐CoV Cyclodepsipeptide Valinomycin in Streptomyces tsusimaensis ATCC 15141 - Cheng, Yi‐Qiang (Chembiochem, 2006)
Valinomycin was recently reported to be the most potent agent against severe acute respiratory‐syndrome coronavirus (SARS‐CoV) in infected Vero E6 cells. Aimed at generating analogues by metabolic engineering, the valinomycin biosynthetic gene cluster has been cloned from Streptomyces tsusimaensis ATCC 15141. Targeted disruption of a nonribosomal peptide synthetase (NRPS) gene abolishes valinomycin production, which confirms its predicted nonribosomal‐peptide origin. Sequence analysis of the NRPS system reveals four distinctive modules, two of which contain unusual domain organizations that are presumably involved in the generation of biosynthetic precursors d‐α‐hydroxyisovaleric acid and l‐lactic acid. The respective adenylation domains in these two modules contain novel substrate‐specificity‐conferring codes that might specify for a class of hydroxyl acids for the biosynthesis of the depsipeptide natural products.